PENTA HELIX MODEL FOR SUSTAINABILITY PERFORMANCE OF PALM OIL PLANTATION COMPANIES IN SOUTH SUMATERA PROVINCE - Katri Gentari; Hamidah, Hamidah; Zulkifli, Zulkifli (International Journal of Social Science, 2024)
The aim of the research is to create and develop a pentahelix model for the sustainability performance of oil palm plantation companies in south Sumatra province and formulate a pentahelix model strategy for the sustainability performance of oil palm plantation companies. The research object involves elements of the pentahelix, namely the government, in this case the south Sumatra province plantation service, academics at the agricultural faculty of Sriwijaya University, the community ,namely Gapki (a combination of oil palm business associations).Businesses are in seven palm oil plantation companies in south Sumatra Province and also online media and offline Sumatra Express.Qualitative methods and analyzing data through soft system methodology. The findings of this research show that there are 3 pillars of oil palm plantation companies that must be considered in developing sustainable performance and to obtain measurable and targeted results they should be included in the vision of long-term development plans. The first is to meet food needs from domestic production, the second is to regulate food policy independently and the third is to the protect and prosfer farmers as the main business actors in palm oil companies.Thereare many strategic matters and issues for the benefit of regional development together with palm oil companies which have a vital role in developing sustainable performance of oil plantation companies that are able to absorb palm oil production.So that companies get a guarantee that the palm oil produced will be absorbed at agood price, conducting training for increasing company productivity throught government supervisory institutions and providing adquateinfrastructure so that distribution run smoothly.Tows analysis illustrates how the external opportunities and threats faced by the company can be adjusted to the company’s strengths and weaknesses.Novelty research is a sustainable performance model and a pentahelix conception model by adding elements of oil palm plantation companies as one of the factors that can be implemented in the sustainable performance of oil palm plantation companies in south Sumatra Province